The Poem Which Lacks the Context. “Vilnius 1943” by Alfonsas Nyka-Niliūnas - Žukas, Saulius (Semiotika, 2021)
The paper focuses on Alfonsas Nyka-Niliūnas’ poem “Vilnius 1943”, written in 1966 when the poet lived in the USA. However, the poem depicts the period of his life in Lithuania when he spent a lot of time in Vilnius. Therefore the paper raises the question of how the authentic living experience influenced the imagery of the poem. It proposes the semiotic reading of the poem that helps to consider the coherence of the imagery and its functions. The semiotic study of the imagery is supplemented with contextual analysis, which differentiates three contextual fields – that of historical context (the war realities), the cultural context (ancient literature, the Bible, Jewish culture, the modern art, etc.) and the context configured by the poet himself. The discussion of the episodes from Nyka-Niliūnas’ biography is based on the diaries, letters and memories of the poet and his relatives. The analysis reveals that it was the historical perspective that influenced the manner of description of holocaust events in the poem. So far as the egological sources allow us to argue, the poetic imagery of the poem is based on the universal historical, cultural and literary contexts rather than significantly influenced by the living experience of the poet in war-time Vilnius.